Pelatihan Bekam di Desa Lekopancing: Upaya Mendekatkan Masyarakat pada Thibbun Nabawi - Dewi Indriani; Asnawati Patuti (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2024)
The Community Service Program (Kuliah Kerja Nyata or KKN) of STIBA Makassar for the VII Batch in Lekopancing Village, Maros Regency, was organized as a manifestation of community service, which is a fundamental pillar of the Tri Dharma of Higher Education. The implementation of this service program began with problem mapping and community needs assessment using SOAR Analysis. After conducting the analysis, work programs were developed according to the community’s needs. Based on the analysis results, several program were formulated, including Al-Qur’an Teaching (TK/TPA), DIROSA, School Teaching Program, Taḥfīẓ Weekend, Muslimah Study Sessions, Ifṭār Distribution, 20-Day Memorization Course, Funeral Management Training, Pious Children Festival, Sakinah Study Sessions, Veil-Wearing Movement, and Sunnah Cupping Therapy. All these programs were successfully implemented and have shown initial results aligned with the objectives of the KKN.